Основні закономірності процесів фільтрації - Дідур, Володимир Володимирович; Didur, Volodymyr; В'юник, Ольга Володимирівна; Viunyk, Olha; Білокінь, Я. В.; Bilokin, Ya.; Петриченко, Є. А.; Petrychenko, Ye. (Запоріжжя: ТДАТУ, 2025)
UA: У цій розглядаються фундаментальні закономірності фільтрації рідин у пористих середови-щах, аналізується межа застосовності класичного закону Дарсі та обґрунтовуються модифікації для неліній-них режимів. Наведено результати огляду сучасних підходів до опису попередньодарсіанських (pre-Darcy) течій, форсхаймерівських (Forchheimer) моделей та мультифазних процесів. На підставі теоретичного ана-лізу та синтезу літератури сформульовано задачі вдосконалення моделі фільтрації з урахуванням неньюто-нівської поведінки рідини та структурних особливостей середовища. Наведено пропозиції щодо подальших досліджень у напрямі чисельної реалізації та верифікації моделей. /// EN: This work examines the fundamental laws of fluid filtration in porous media, analyzes the limits of applicability of the classical Darcy’s law, and justifies modifications for nonlinear flow regimes. A review of modern approaches to describing pre-Darcy flows, Forchheimer models, and multiphase processes is presented. The paper graphically shows the deviation from the linear law of filtration: the dependences of the change in the reduced resistance coefficient C_F on the Reynolds number Re during the movement of a viscous fluid through the structure of a porous material and the dependence of the filtration flow velocity V on the pressure gradient I when distilled water passes through a hydrophilic porous structure are given. The nature of the change in the strain rate ε ̇ depending on the shear stress τ: for liquids with different physical properties is also graphically presented. Based on theoretical analysis and literature synthesis, tasks are formulated to improve filtration models by accounting for the non-Newtonian behavior of fluids and the structural features of the medium. Proposals for further research are provided, focusing on numerical implementation and model verification.
Fundamental regularities of filtration processes
Keywords: фільтрація; закон Дарсі; нелінійна фільтрація; pre-Darcy; модель Форсхаймера; пористе середовище; в’язкість; модифікована модель; filtration; Darcy’s law; nonlinear filtration; Forchheimer model; porous medium; viscosity; modified model